+0  
 
0
38
1
avatar

Let $a,$ $b,$ $c$ be positive real numbers such that \[\log_a b + \log_b c + \log_c a = 0.\]Find \[(\log_a b)^3 + (\log_b c)^3 + (\log_c a)^3.\]

 Jun 29, 2021
 #1
avatar+120966 
+1

Using the  change of base rule

 

Let  x =  log b/ log a        y  = log c / log b        z =   log  a / log c 

 

x +  y  +  z  =  0

x + y    =   -z               square both sides

x^2 + y^2  + 2xy   =  z^2

x^2 + y^2   =  z^2   - 2xy

 

x^3  +  y^3   +  z^3   =

(x + y)  ( x^2  - xy + y^2)  +  z^3   =  

(-z) ( z^2 - 2xy - xy)  + z^3    = 

(-z) ( z^2  -  3xy)  + z^3   = 

-z^3  + 3xyz  + z^3    =

 

3xyz   =

 

3  [ log b / log a  ]  [ log c / log b   ]   [ log a / log c]  =

 

3 [ log a/ loga ]   [ log b  /log b  ] [ log c / log c  ]   =

 

3 [ 1] [ 1 ] [ 1 ] = 

 

3

 

 

cool cool cool

 Jun 29, 2021
edited by CPhill  Jun 29, 2021

14 Online Users